SEC Attention, A to Z - Stice‐Lawrence, Lorien (Contemporary Accounting Research, 2026)
ABSTRACT I use downloads of regulatory filings by SEC employees as a measure of SEC attention and find that SEC employees are disproportionately less likely to review the filings of firms with names later in the alphabet. Additional tests show that alphabetical order determines a firm's priority when the SEC follows up on common shocks among peer firms and that the strength of the SEC's alphabetical bias does not vary with the intensity of resource constraints. Further, the SEC appears to be more surprised by the restatements of end‐of‐the‐alphabet firms. These results are consistent with a cognitive bias that leads SEC employees to pay more attention to firms at the top of alphabetically sorted lists. Last, using shocks to alphabetical order caused by firm name changes, I find that alphabetically induced increases in SEC attention are linked with lower future noncompliance, suggesting that the regulatory effects of alphabetical order are material. Overall, this study highlights the “human” element of regulatory attention.